2016
DOI: 10.1007/s13762-016-1006-3
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of azo dyes from aqueous solutions by natural bentonite under static and dynamic flow conditions

Abstract: This work reports new findings on the physisorption of Foron Blue 291 on natural bentonite under both static and dynamic flow conditions of the aqueous solution that may prove important when using the adsorption technique for wastewater treatment. The quantity of dye retained by the solid matrix under both ideal exchange conditions between dyes and adsorbents given in a batch reactor and a pulse injection of dissolved azo dye in a soil column composed of a mixture of mean grain-sized sand and bentonite at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Two configurations have been investigated with either pollutant originating from the sediment or the overlying water. Saline solution (NaCl) was used as a pollutant for the conservative tracer and the dye FB291 (CAS Number: 56548-64-2) was used as a strongly sorptive molecule (Berez et al, 2016). The combination of tracers with different sorptive properties allowed to distinguish between organic pollutant transport and phase partitioning in lab-scale constructed wetlands (Fernandez-Pascual et al, 2020).…”
Section: Conservative and Sorptive Tracer Experimentsmentioning
confidence: 99%
“…Two configurations have been investigated with either pollutant originating from the sediment or the overlying water. Saline solution (NaCl) was used as a pollutant for the conservative tracer and the dye FB291 (CAS Number: 56548-64-2) was used as a strongly sorptive molecule (Berez et al, 2016). The combination of tracers with different sorptive properties allowed to distinguish between organic pollutant transport and phase partitioning in lab-scale constructed wetlands (Fernandez-Pascual et al, 2020).…”
Section: Conservative and Sorptive Tracer Experimentsmentioning
confidence: 99%
“…Due to it being naturally occurring and easily available, bentonite (Bent) has attracted significant interest as an adsorbent. Berez et al reported the wastewater treatment by the physisorption of Foron Blue 291 on natural bentonite under both static and dynamic flow conditions of the aqueous solution [ 36 ], while the poor dispersibility of the natural Bent limited its adsorption property. In order to improve its dispersibility, some special functional groups should be modified onto a Bent surface to enhance the adsorption amount of the natural Bent.…”
Section: Introductionmentioning
confidence: 99%
“…Dyes are widely used in different industries such as textile, pigment, cosmetics, food stuffs, etc., and more than 8000 chemically different types of dyes are employed in these industries . It is estimated that color production levels are about 800 000 tons/year . Most dyes are synthetic and complex organic chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] It is estimated that color production levels are about 800 000 tons/year. [3] Most dyes are synthetic and complex organic chemicals. High amount of dye in effluents affect the photosynthetic action of plants.…”
Section: Introductionmentioning
confidence: 99%